Apoptosis en tumor venéreo transmisible del canino en fase de crecimiento progresivo y durante regresión inducida por vincristina - González, Carlos; Cepeda, Raquel; Flores, Estefanía; Cattaneo, Gino; Reyes, Susana (Avances en Ciencias Veterinarias, 2003)
Apoptosis or programmed cell death is a mechanism of cell elimination when they are unnecessary or genetically damaged. It is controlled by a variety of genes, many of which present mutation or dysfunstion associated to cancer. When this occurs patients have more aggressive tumors. A characteristic DNA fragmentation occurs during apoptosis which can be traced and enzimatically revealed by TÚNEL (terminal transference mediaded dUTP-biotin nick end labelling) technique. This allows early apoptosis detection even before the first morphologic nuclear changes take place. In this work 10 adult canine with genital TVT were selected to undergo one single doce (0.03mg/Kg) Vincristine sulphate treatment, in arderto induce tumor regression. Histological samples were obtained and processed for TÚNEL immune staining. Images were digitalized an analyzed by a morphometric software (Image Pro-Plus, Media Cybernetics, USA). The mean area obtained for apoptotic cells was 51.3±37.9mm2 and 1396±828.6mm2/200X field, for progressive and regressive growth, respectively. This indicates a significant dference between both phases (p<0.0001). The main cell type for both tumor stages corresponded to tumor cells with 80,7% for progressive and 89.4% for regressive growth, resulting in a sign ficant augmentation for this latter tumor stage (p<0.001). This results indicate that vincristine induces TVT to collapse through apoptosis. The exact underlying mechanism remains to be demonstrated, however in other neoplams caspasas 9 and 3 activation has been described suggesting that the mitochondrial way is involved, through oxgygen derived radical production and Bcl-2 gene overexpression.